The contributions of Indigenous People's earth observations to water quality monitoring - López-Maldonado, Yolanda; Anstee, Janet; Neely, Merrie Beth; Marty, Jérôme; Mastracci, Diana; Ngonyani, Happyness; Ogashawara, Igor; Salyani, Anham; Sharma, Kabindra; Sims, Neil C. (Frontiers in Water, 2024)
Indigenous Knowledge, observations and understandings of earth processes are not sufficiently included in global Earth Observations. Drawing on the results obtained during a three-day hackathon event, we present evidence, best practices and recommendations to water quality organizations seeking to engage and share information with Indigenous communities. The hackathon event revealed three key findings: First, Indigenous Peoples report precise and accurate observations of changes in various Earth systems, particularly the hydrological cycle. Second, this information can significantly enhance global Outreach and Engagement efforts, aiding in the understanding of hydrological cycle components, water quality, mapping water courses, and monitoring and mitigating the effects of climate change (i.e., floods, droughts, etc.). Third, enabling Indigenous Peoples to contribute their scientific knowledge and utilize Earth Observations is crucial for the protection of other vital components of the water cycle. We addressed crucial questions: What opportunities exist to include Indigenous Knowledge into Earth Observations and what are the main challenges in doing so?